2008
DOI: 10.1016/j.chembiol.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Design of Peptide Inhibitors for the Importin α/β Nuclear Import Pathway by Activity-Based Profiling

Abstract: Despite the current availability of selective inhibitors for the classical nuclear export pathway, no inhibitor for the classical nuclear import pathway has been developed. Here we describe the development of specific inhibitors for the importin alpha/beta pathway using a novel method of peptide inhibitor design. An activity-based profile was created via systematic mutational analysis of a peptide template of a nuclear localization signal. An additivity-based design using the activity-based profile generated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 43 publications
6
178
1
Order By: Relevance
“…The amino acid substitution analyses of importin-␣-dependent NLSs in our previous and present studies have demonstrated that the contribution of each residue to the overall NLS activity is, in most cases, independent and additive (14). Fig.…”
Section: Accurate Prediction Of Nls Activity By Scoring With the Nls mentioning
confidence: 99%
See 3 more Smart Citations
“…The amino acid substitution analyses of importin-␣-dependent NLSs in our previous and present studies have demonstrated that the contribution of each residue to the overall NLS activity is, in most cases, independent and additive (14). Fig.…”
Section: Accurate Prediction Of Nls Activity By Scoring With the Nls mentioning
confidence: 99%
“…We have recently shown that, even within the same NLS class, the level of NLS activity varies depending on the NLS sequence (5,14). To assess the functional contribution of various amino acids at every position in each of 3 monopartite NLS classes (classes 2-4) (5), all of the amino acid residues of the template NLSs, as representatives of these classes, were serially replaced with Ϸ20 other amino acid residues.…”
Section: Activity-based Profiles Of Different Classes Of Importin-␣-dmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the NOCT orthologs in Fig. 3 using NucPred [96], cNLS Mapper [9799], and SeqNLS [100] tools did not predict nuclear localization, whereas PSORTII [101,102] predicted nuclear localization for Drosophila, X. laevis , and D. rerio NOCTB orthologs. Mitochondrial localization is predicted for several NOCT orthologs.…”
Section: Is Noct Activity Spatially Restricted?mentioning
confidence: 99%